Exchange-Rate Swings and Foreign Currency Intervention - Filardo, Andrew; Gelos, R.; McGregor, Thomas (Washington, D.C. : International Monetary Fund, 2022)
This paper develops a new approach for exploring the effectiveness of foreign currency intervention, focusing on real exchange cycles. Using band spectrum regression methods, it examines the role of macroeconomic fundamentals in determining the equilibrium real exchange rate at short-, medium-, and low frequencies. Next, it assesses the effectiveness of FX intervention depending on the degree of cycle-specific misalignments for 26 advanced- and emerging market economies, covering the period 1990-2018, and using different techniques to mitigate endogeneity concerns. Evidence supports the hypothesis that central banks can lean effectively against short-run cyclical misalignments of the real exchange rate. The effects are present in quarterly data-i.e., at policy-relevant horizons. The effectiveness of intervention rises with the size of the misalignment, and with the duration of one-sided interventions. FX sales appear to be somewhat more effective than FX purchases, and intervention is less effective in more liquid FX markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Central Banks and Their Policies; Foreign Exchange; International Finance Forecasting and Simulation